Durability of geopolymer stabilized domestic waste incineration slag blending macadam in pavement base - Ji, Xiaoping; Mou, Keliang; Zhang, Ting; Dong, Xinze (Frontiers in Materials, 2023)
In order to achieve the high quality and large-scale utilization of domestic waste incineration slag (WIS) in pavement base, a geopolymer prepared using fly ash from domestic waste incineration was used to replace the cement to stabilized WIS blending macadam used in the pavement base. The durability of the geopolymer stabilized WIS blending macadam (called as GeoWIS) was investigated, including the water stability, freeze-thaw resistance and dry shrinkage. The strength formation was identified using SEM analyses. Furthermore, the durability of GeoWIS was investigated and compared with those of cement stabilized macadam (CSM). Results show that the 7 days compressive strength of GeoWIS meets the strength criterion of the asphalt pavement base (≥ 2 MPa), except for the combination of 8% geopolymer and 100% WIS. The water stability coefficient and residual compressive strength ratio of GeoWIS increase as the geopolymer increases and WIS decreases. The cumulative dry shrinkage and dry shrinkage coefficient decrease as the WIS increases, while the cumulative water loss rate of GeoWIS increases. SEM analysis shows that the geopolymer reaction generates C-S-H gels, N-A-S-H gels, and Aft, which is the source of the GeoWIS strengths. GeoWIS has better water stability than CSM, and its freeze-thaw resistance and average dry shrinkage coefficient are lower than the average values for CSM.